A Gender book to enhance Writing Skills through PBL. (2024)
This research was conducted at Colegio La Merced with 25 eleventh-grade students aged 16 to 17. It aimed to evaluate the impact of Project-Based Learning (PBL) on improving EFL students’ writing skills through the creation of a gender issues book in English. Following the principles of action research, the study was carried out in two cycles of ten sessions each. Data was collected via surveys, field notes, workshops, and a test. Analysis using a triangulation method revealed a significant improvement in students’ writing abilities, highlighting the effectiveness of PBL in enhancing their writing proficiency.